Exploring polyoxometalates as non-destructive staining agents for contrast-enhanced microfocus computed tomography of biological tissues. (15th March 2020) - de Bournonville, Sébastien; Vangrunderbeeck, Sarah; Ly, Hong Giang T.; Geeroms, Carla; De Borggraeve, Wim M.; Parac-Vogt, Tatjana N.; Kerckhofs, Greet
Abstract: To advance clinical translation of regenerative medicine, there is, amongst others, still need for better insights in tissue development and disease. For this purpose, more precise imaging of the 3D microstructure and spatial interrelationships of the different tissues within organs is crucial. Despite being destructive towards the sample, conventional histology still is the gold standard for structural analysis of biological tissues. It is, however, limited by 2D sections of a 3D object, prohibiting full 3D structural analysis. MicroCT has proven to provide full 3D structural information of mineralized tissues and dense biomaterials. However, the intrinsic low X-ray absorption of soft tissues requires contrast-enhancing staining agents (CESAs). In a previous study, we showed that hafnium-substituted Wells-Dawson polyoxometalate (Hf-WD POM) allows simultaneous contrast-enhanced microCT (CE-CT) visualization of bone and its marrow vascularization and adiposity. In this study, other POM species have been examined for their potential as soft tissue CESAs. Four Wells-Dawson POMs, differing in structure and overall charge, were used to stain murine long bones and kidneys. Their staining potential and diffusion rate were compared to those of Hf-WD POM and phosphotungstic acid (PTA), a frequently used but destructive CESA. Monolacunary Wells-Dawson POM (Mono-WD POM) showed similar soft tissue enhancement as Hf-WD POM and PTA. Moreover, Mono-WD POM is less destructive, shows a better diffusion than PTA, and its synthesis requires less time and cost than Hf-WD POM. Finally, the solubility of Mono-WD POM was improved by addition of lithium chloride (LiCl) to the staining solution, enhancing further the soft tissue contrast. Statement of Significance: To advance clinical translation of regenerative medicine, there is, amongst others, still need for better insights in tissue development and disease. For this purpose, more precise imaging of the 3D microstructure and spatial interrelationships of the different tissues within organs is crucial. Current standard structural analysis techniques (e.g. 2D histomorphometry), however, do not allow full 3D assessment. Contrast-enhanced X-ray computed tomography has emerged as a powerful 3D structural characterization tool of soft biological tissues. In this study, from a library of Wells Dawson polyoxometalates (WD POMs), we identified monolacunary WD POM together with lithium chloride, dissolved in phosphate buffered saline, as the most suitable contrast-enhancing staining agent solution for different biological tissues without tissue shrinkage. Graphical abstract: Image, graphical abstract